Great expectations [videorecording (DVD)] - Lean, David, 1908-1991; Mills, John, 1908-2005; Hobson, Valerie, 1917-1998; Miles, Bernard, 1907-1991; Sullivan, Francis L.; Hunt, Martita, 1900-1969; Guinness, Alec, 1914-2000; Simmons, Jean, 1929-2010; Dickens, Charles, 1812-1870 (Criterion collection, 1998)
In the gloom of a country graveyard, a young boy encounters an escaped convict, a chance meeting that years later leads the boy to tragedy, mystery and wealth.